Analysis of Environmental Communication in Waste Management Efforts in Palu - Akifah, Andi; Saldi, Ferawaty; Ningsih, Fitriany Puspa (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2024)
This study aims to provide information and become a reference for other parties in developing effective communication methods in waste management. Thus, the waste problem in Palu City can be overcome more efficiently, and the community can be more aware of environmental cleanliness. By involving active participation from all parties, including the community and society, waste management efforts can succeed, and Palu City will become cleaner and healthier. The research method used is a qualitative method that produces descriptive data in the form of written or spoken words and observable behavior. This approach describes the social world from the point of view of the individual or the informant's interpretation in a scientific context. Informants were selected based on purposive sampling techniques with selection based on predetermined criteria, namely Seangle's permanent administrators, who have joined since the beginning of the community's establishment in 2017, the Palu City Environmental Agency, and participants in Seangle's work programs. The results showed that the work program carried out by Seangle had provided positive changes to people's habits, which, although not measured in concrete data, observationally look significant from time to time. The motivation given by Seangle through a persuasive attitude aroused community participation to build positive habits toward waste management in Palu City jointly.